2017
DOI: 10.11114/ijsss.v5i9.2523
|View full text |Cite
|
Sign up to set email alerts
|

Moving on: Multiple Transitions of Unaccompanied Child Migrants Leaving Care in England and Sweden

Abstract: This paper explores the priorities of young people who arrived in England or Sweden as unaccompanied minors and are leaving the care of the state to transition to adult life. Policy and practice for these young pe ople are themselves in transition in Europe, and we aim to contribute to the slender first person qualitative evidence base for those delivering services. Our methods comprised a scoping review of scholarly and grey literature, and group and individual interviews. Despite a commitment in both countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In 2015, we undertook a participatory study of care leavers’ health and social care needs in England with 24 ethnically diverse care leavers some of whom had arrived as unaccompanied minors (Liabo et al, 2017). The following year, we carried out individual interviews with unaccompanied young migrants and learning disabled care leavers (see Roberts et al, 2017). As part of these follow-ups, a scoping review of UK and Swedish grey and scholarly literature (in English and Swedish) was undertaken, focussing on care leavers’ accounts of their health needs and priorities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, we undertook a participatory study of care leavers’ health and social care needs in England with 24 ethnically diverse care leavers some of whom had arrived as unaccompanied minors (Liabo et al, 2017). The following year, we carried out individual interviews with unaccompanied young migrants and learning disabled care leavers (see Roberts et al, 2017). As part of these follow-ups, a scoping review of UK and Swedish grey and scholarly literature (in English and Swedish) was undertaken, focussing on care leavers’ accounts of their health needs and priorities.…”
Section: Methodsmentioning
confidence: 99%
“…First-hand accounts from young migrants regarding their own health and welfare needs and priorities are lacking and the limited evidence shows that young migrants prioritised the determinants of health such as education, employment and housing rather than access to clinical services. The vital role of a trusted and caring contact, whether friend, health or social care provider, carer or official guardian, was underlined for Swedish and British settings (Roberts et al, 2017).…”
Section: Scoping Review -Young People's Concerns About Health and Heamentioning
confidence: 99%
“…In 2015, we carried out a participatory study on the multiple transitions out of the care system of young people in an inner city local authority in England (Liabo et al, 2016). We found that two groups, youngsters with learning disabilities and unaccompanied migrants (Roberts et al, 2017), faced more than their fair share of challenges.…”
Section: Introductionmentioning
confidence: 99%